Popular Music Scenes
XXXI, 253 p. 12 illus., 9 illus. in color.
Keywords: This book examines regional and rural popular music scenes in Europe, Asia, North America and Australia. The book is divided into four parts. Part 1 will focus on the spatial aspects of regional popular music scenes and how place and locality inform the perceptions and discourses of those involved in such scenes. Part 2 focuses on the technologies and forms of distribution whereby regional and rural popular music scenes exist and, in many cases co-exist in forms of trans-local connection with other scenes. Part 3 considers the importance of collective memory in the way that regional and rural popular music scenes are constructed in both the past and the present. Part 4 examines themes of industry and policy, in relation to culture and music, as these impact on the nature and identity of rural and regional popular music scenes. Andy Bennett is Professor of Cultural Sociology in the School of Humanities, Languages and Social Science at Griffith University in Queensland, Australia. He has written and edited numerous books including Popular Music and Youth Culture, Music, Style and Aging and Music Scenes (co-edited with Richard A. Peterson). David Cashman is an Adjunct Associate Professor of Contemporary Music at Southern Cross University. He writes on regional music scenes, live popular music, and music and tourism. Ben Green is a Postdoctoral Research Fellow of the Griffith Centre for Social and Cultural Research at Griffith University in Queensland, Australia. He is the author of Peak Music Experiences: A New Perspective on Popular Music, Identity and Scenes. Natalie Lewandowski is an Adjunct of the Creative Arts Institute at Griffith University in Queensland, Australia. Her experience working across government, the arts, academia and commercial industries has resulted in publications and engagement with film sound, music sustainability, music and wellbeing.